INVESTIGATING SAFETY MANAGEMENT PRACTICES, PERFORMANCE AND TURNOVER INTENTIONS IN VIETNAMESE MIGRANT WORKERS - Duc, Tran Hong; Lu, Te-Tsai (Graduate Program of Universitas Tarumanagara, 2025)
Vietnamese migrant workers are currently one of the largest groups of migrant workers in Taiwan. As the number of Vietnamese migrant workers increases, the safety problems they face are becoming more obviously. According to statistics, Vietnamese migrant workers account for 50.87% of the total occupational accidents among foreign migrant workers. This study aims to examine how Vietnamese migrant workers perceive various factors by investigating the connections between safety management practices, safety performance, and turnover intentions. The goal is to address safety concerns more effectively. To gather data, a questionnaire survey method was utilized. Out of 450 distributed questionnaires, 413 valid responses were received. Through quantitative analysis, the study revealed that enhancing safety management practices and performance significantly reduces the likelihood of turnover among Vietnamese migrant workers. Notably, reinforcing safety promotion policies yields particularly strong effects. To further improve safety management, this study suggests that companies establish a reward system to motivate employees to report and address safety issues. Furthermore, the managers of the company should make specific improvements to safety matters reported by employees.